A Simple Precracking Procedure for Fracture Toughness Testing In Rock - Application to Roof Rock Above No. V Coal (Indiana) - Mark A. Travers; Thomas M. Tharp (Society for Mining, Metallurgy & Exploration, 1986)
A new method is presented for precracking three-point bending specimens for fracture toughness testing. A notched specimen of rectangular cross section is placed on a flat loading platen, with paper between specimen and platen. The specimen is loaded from above through a roller placed directly over the crack. The thin, high compliance joint between specimen and platen causes a distributed load on the bottom of the specimen. This results in bending at the cracked section and crack initiation at the notch tip. Since the joint is thin, its stiffness increases rapidly with deflection and crack propagation in the specimen generally remains stable and controllable. Fracture toughness KIC in a sandstone directly overlying the No. V coal was measured to be 0.27 MPa m 1/2. Even for cracks 1 cm long this value of KIC results in substantially lower effective tensile strength (modulus of rupture) in roof beams than is expected from intact rock strength.